Relationship of agricultural production and agricultural credit guarantee scheme fund in nigeria: a causality analysis - OYAKHILOMEN, OYINBO; G, REKWOT; G ATIM, ADEGBOYE (Journal of Management and Science, 2013)
This study was carried out to examine the causality of agricultural production and the Agricultural Credit Guarantee Scheme Fund(ACGSF) in Nigeria. ADF unit root test, unrestricted VAR and granger causality test were employed in the analysis of the dataset and result showed that there is no causality between agricultural production and value of agricultural credit guaranteed but a unidirectional causality from agricultural production to the number of agricultural credit guaranteed existed. This implies that we can better predict the outcome of agricultural production in Nigeria using the past values of the number of agricultural credit guaranteed.